Documentation of flowering plants and ethnobotany in Jhilmil Lake area, Kanchanpur, Sudurpaschim Province - Bhatt, Man Dev; Joshi, Dirgha Raj; Bhandari, Gauri Shankar; Maharjan, Sujan; Guragain, Dipesh; Tamang, Pasang; Kunwar, Ripu Mardhan (Banko Janakari, 2023)
Documentation of indigenous knowledge about plants plays a key role for conservation and utilization of plant resources. The present paper documents the diversity of plants and their traditional use in and around the Jhilmil Lake Area, one of the forest-dominated peri-urban areas of Kanchanpur district lying in Sudurpaschim Province. Vegetation sampling and ethnobotanical surveys were carried out twice between January, 2020 and January, 2021. Semi-structured questionnaire and checklists were used to record the use and distribution of the plant species and their conservation. A total of 126 plant species representing 52 families and 113 genera were reported. Among the total plants recorded, 114 (90.48 %) species were found to be ethnomedicinally used. The results showed that the use of plants as ethnomedicine was culturally motivated and less influenced by availability of the plants. The plant “importance value index” (IVI) was found to be negatively associated with the plant “relative frequency of citation” (RFC; p=0.057–0.790). The high RFC values of the trees and climbers hinted that the plant collection was subjectively oriented towards quality products. The findings suggested that the rare plants with high-use values such as Pterocarpus marsupium, Dalbergia latifolia, Rauvolfia serpentina, Citrus limonum, and Mussaenda frondosa should be prioritised for future conservation. It illustrates that lakes in forested areas are essential resources for plant diversity and local life because they include a variety of rare and useful local plant species